The price of addiction: Pakistani children paying the cost of tobacco use with their temperament - Rasheed, Muhammad Sameer; Imran, Sadia Muhammad Imran; Younus, Javeria Younus (Journal of the Pakistan Medical Association, 2023)
Madam, Tobacco smoking is a significant public health concern and a leading cause of morbidity and mortality worldwide. According to the World Health Organization (WHO), 942 million men and 175 million women aged 15 or older smoke tobacco and more than seven million people per annum die due to tobacco usage. In Pakistan, the prevalence of tobacco smoking is reported to be 13.4%, according to the NDSP survey (1) Research has shown that exposure to second and third-hand smoke can adversely effect children’s temperament and neurobehavioral outcomes. For instance, a study using the 2007 NSCH found that children exposed to second or third-hand smoke are at a 50% increased risk of developing neurobehavioral disorders such as ADHD or learning disabilities (2). Furthermore, E. Melinda et al. reported that exposure to tobacco smoke in children led to a statistically significant increase in developmental delay along with depression, intellectual learning and speech disabilities among others. (3) Childhood temperament has also been found to significantly impact adult temperament, as demonstrated by a cohort study that followed children from 3 years onwards to 26 years of age. Children classified as under-controlled at age 3 went on to display irritable, impulsive, emotionally labile, and unpredictable personality traits as adults. Similar correlations were found in children labelled as inhibited. Other temperament groups such as confident, reserved, and well-adjusted did not show significant personality profile changes, but a noticeable continuity was observed in each group (4). To decrease children's exposure to tobacco, parental awareness campaigns may be helpful. An RCT by Viki Myers et al. found that educating parents exploratively about tobacco exposure led to changes in parental smoking behaviour (5). So raising parental cognisance, essentially, can decrease neurobehavioral and temperamental issues in children and ultimately, adults. Hence, continually raising awareness about the detrimental effects of exposing children and individuals to tobacco smoking is a key method to reform a healthy environment for children.